Fuzzy Control of a Robotic Arm using EMG Signals - Hidalgo, M. (2007)
This paper presents the control design of a robotic arm employing Fuzzy algorithms to interpret electromiographic (EMG) signals from the Flexor Carpi Radialis, Extensor Carpi Radialis and Biceps Brachii muscles. The control and aquisition systems is composed of a microprocessor, analog ﬁltering, digital ﬁltering and frequency analysis, and ﬁnally a fuzzy control system. The system has been implemented over a MICROCHIP PIC 16F876 and LabVIEW.